Top 100 most-cited publications in hidradenitis suppurativa: An updated bibliometric analysis - Teng, Yan; Li, Sujing; Fan, Yibin; Tao, Xiaohua; Huang, Youming (Frontiers in Medicine, 2022)
Background: Over the last several decades, our understanding of hidradenitis suppurativa (HS) has improved considerably, thereby enhancing our ability to clinically diagnose and treat the disease. Objective: The purpose of this study was to identify and analyze the top 100 most-cited publications related to HS to update bibliometric information on HS. Methods: We used the Web of Science database to identify reports on hidradenitis suppurativa. Data from the 100 most cited publications were extracted and analyzed. Results: The citation number of the top 100 most-cited articles was 89–532 (mean, 153.51), with the most productive periods being from years 2007 to 2016. Most publications originated from the British Journal of Dermatology and the Journal of the American Academy of Dermatology. The 100 articles originated from 18 countries, with Denmark being the most productive country, followed by the United States (17), England (14), and Germany (12). Jemec GB, from the University of Copenhagen, had 32 citations and was the most frequently identified author. The 100 articles encompassed several fields of research as follows: pathogenesis (18%), pathophysiology (7%), epidemiology (14%), clinical diagnosis and features (16%), treatment (25%), comorbidity (10%), and others (10%). In total, 11 reviews, three guidelines, and 86 original articles (9 randomized clinical trials) were included. Conclusion Through this bibliometric analysis, we aimed to indicate a series of intellectual landmark publications that offer us critical reviews, guidelines, and original articles, which highlight the immense level of progress achieved in the field of HS.